A single bout of physical exercise does not affect young adults' executive functions - Gentile Ambra; Thomas Ewan; Feka Kaltrina; Di Vincenzo Anita; Restifo Marco; Amata Valentina; Alesi Marianna; Drid Patrik; Maksimovic Nebojsa; Bianco Antonino; Boca Stefano (Sciendo, 2020)
Study aim. The purpose of the current study is to determine the impact of single bouts of physical exercise of different duration and intensity on young adults' executive functions.